Differential expression profiling of tRNA-Derived small RNAs and their potential roles in methamphetamine self-administered rats - Zhou, Yun; Hong, Qingxiao; Xu, Wenjin; Chen, Weisheng; Xie, Xiaohu; Zhuang, Dingding; Lai, Miaojun; Fu, Dan; Xu, Zemin; Wang, Majie; Zhou, Wenhua; Liu, Huifen (Frontiers in Genetics, 2023)
Transfer RNA-derived small RNAs (tsRNAs) are a novel class of short, noncoding RNAs that are closely associated with the pathogenesis of various diseases. Accumulating evidence has demonstrated their critical functional roles as regulatory factors in gene expression regulation, protein translation regulation, regulation of various cellular activities, immune mediation, and response to stress. However, the underlying mechanisms by which tRFs & tiRNAs affect methamphetamine-induced pathophysiological processes are largely unknown. In this study, we used a combination of small RNA sequencing, quantitative reverse transcription-polymerase chain reaction (qRT‒PCR), bioinformatics, and luciferase reporter assays to screen the expression profiles and identify the functional roles of tRFs and tiRNAs in the nucleus accumbens (NAc) of methamphetamine self-administration rat models. A total of 461 tRFs & tiRNAs were identified in the NAc of rats after 14 days of methamphetamine self-administration training. Of those, 132 tRFs & tiRNAs were significantly differentially expressed: 59 were significantly upregulated, whereas 73 were significantly downregulated in the rats with methamphetamine self-administration. Decreased expression levels of tiRNA-1-34-Lys-CTT-1 and tRF-1-32-Gly-GCC-2-M2, as well as increased expression levels of tRF-1-16-Ala-TGC-4 in the METH group compared with the saline control were validated by using RT‒PCR. Then, bioinformatic analysis was performed to analyse the possible biological functions of tRFs & tiRNAs in methamphetamine-induced pathogenesis. Furthermore, tRF-1-32-Gly-GCC-2-M2 was identified to target BDNF using the luciferase reporter assay. An altered tsRNA expression pattern was proven, and tRF-1-32-Gly-GCC-2-M2 was shown to be involved in methamphetamine-induced pathophysiologic processes by targeting BDNF. The current study provides profound insights for future investigations to explore the mechanisms and therapeutic methods for methamphetamine addiction.